(untitled) ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2025)
Communicative Language Teaching (CLT) has gained widespread recognition as a powerful approach in the field of English language teaching, particularly in fostering learners’ speaking proficiency and autonomy. This thesis investigates the theoretical foundations, classroom applications, and measurable outcomes of CLT in ESL contexts. By examining the pedagogical shift from traditional grammar-based methods to communicative frameworks, the study explores how learners become active participants in their own learning and develop the confidence to use English in real-life situations.